2017
DOI: 10.4012/dmj.2016-148
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of direct pulp capping with all-in-one adhesives in rat teeth

Abstract: The aim of this study was to histologically evaluate direct pulp capping using different all-in-one adhesives in rat teeth. Five allin-one adhesives and a control material (MTA) were used. Each material was applied on the exposed pulp, and each cavity was subsequently restored with the resin composite. Rats were sacrificed 14 days after the surgical procedure. Serial stained sections were histologically evaluated for examining pulp tissue disorganization (PTD), inflammatory cell infiltration (ICI), dentin brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…DMP1 plays an important role in odontoblast differentiation and matrix mineralization (Kaida et al, 2008). As shown in Figure 5, the positive staining of DMP1 determined the MTBF, indicating favourable induction potential of MTAPPL and NCMTA on the proliferation of stem cells, their migration to the exposed pulp surface and their differentiation into odontoblast cells as shown in other studies (Shinkai et al, 2017). CD34 is an endothelial marker extensively used in IHC procedures.…”
Section: Discussionsupporting
confidence: 71%
“…DMP1 plays an important role in odontoblast differentiation and matrix mineralization (Kaida et al, 2008). As shown in Figure 5, the positive staining of DMP1 determined the MTBF, indicating favourable induction potential of MTAPPL and NCMTA on the proliferation of stem cells, their migration to the exposed pulp surface and their differentiation into odontoblast cells as shown in other studies (Shinkai et al, 2017). CD34 is an endothelial marker extensively used in IHC procedures.…”
Section: Discussionsupporting
confidence: 71%
“…Jun et al ( 35 ), evaluated the biological properties of the biomonomer without BIS-GMA, which they developed to avoid the estrogenic and cytotoxic effects of BIS-GMA, reported that the biomonomer they developed had a high viability level of human oral keratinocyte and MCF-7 cells. Shinkai et al ( 36 ), evaluated the toxicity of resin-containing adhesives in the pulp reported that dental adhesives containing HEMA and TEDGMA showed more severe inflammation. However, they reported that the permeability of the adhesive monomers to the pulp tissue and the degree of polymerization of the adhesives may also be related to the irritation of the pulp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum number of samples needed to identify differences between groups was tentatively determined based on the previous study 12) and resource equation approach 13) , then confirmed by calculation using the program G*Power version 3.1.9.4 (Faculty of Mathematics and Natural Sciences, Dusseldorf, Germany) for the t-test conditions of two dependent samples, alpha error 0.05, power 0.90 and the ratio of the number of experimental animals. Due to the absence of previous studies that calculated actual coordinate shifts of fiducial points delineated on pulp cavity outlines, the effect size was determined based on the previous study comparing direct pulp capping with dentine adhesives and ProRoot MTA (as control) 14) and the pilot quantitative results of our experiment. Since the results of the two groups in each experiment (direct pulp capping, ProRoot MTA vs. dentin adhesive; inducing apical periodontitis, intentional lesion inducing vs. normal tooth without intervention) were apparently distinguished from each other, the effect size was calculated as >2 numerically.…”
Section: Animals and Treatmentsmentioning
confidence: 99%